Decline in acute upper gastrointestinal bleeding during COVID-19 pandemic after initiation of lockdown in Austria - Schmiderer, Andreas (Endoscopy, 2020)
Background  COVID-19 has spread rapidly around the world. The Austrian government implemented a lockdown on 16 March to contain further spread of the disease. We investigated the effects of lockdown on acute upper gastrointestinal (GI) bleeding in Austria. Methods  We contacted 98 Austrian hospitals performing emergency endoscopies. The hospitals were asked to report upper GI endoscopies performed for recent hematemesis, melena, or both, and exhibiting endoscopically visible signs of bleeding. The study period was from 3 weeks before (calendar Week 9) to 3 weeks after (Week 14) initiation of the lockdown. Results  61 % of Austrian hospitals, and importantly all major state hospitals, responded. A total of 575 upper GI bleedings occurred during the 3 weeks before and 341 during the 3 weeks after initiation of lockdown (40.7 % reduction). There was a 54.6 % decline in nonvariceal bleeding events at Week 14 compared with Week 9 (89 vs. 196), whereas rates of variceal hemorrhage did not change (15 vs. 17). Conclusions  National lockdown resulted in a dramatic decrease in upper GI bleeding events in Austrian hospitals.